Never Post-Racial: The Persistence of the Dual State. (4th July 2018) - Witt, Matthew T.
Abstract : Following the riots of the 1960s in major U.S. cities and the 1968 Kerner Commission Report, some public administration scholars initiated a limited focus on race themes in public administration. Today, mass incarceration serves more purposes than the kettling and destruction of young men of color or capital accumulation through the private prison complex and real property appropriation. Through linkages to immigration and terrorism, race is now resurgent as a key signifier of state legitimacy. The Black Lives Matter movement now heightens the urgency for public administration scholars to renew examination of enduring themes of race and public service (Blessett, Gaynor, Witt, & Alkadry, 2016 ). Although there is substantial scholarship produced by critical race theorists on the role that race has played in forming and sustaining institutions in the United States (cf. Delgado & Stafancic, 2013 ), with few exceptions (Alkadry & Blessett, 2010 ; Stivers, 2007 ) mainstream public administration scholarship has not closely examined how historic influences reproduce racialized social stratification in the United States. This article identifies how institutional practices in the United States emerge from and serve "dual state" practices and commitments founded on and devoted to recapitulating a racialized social contract.